The Contrapuntal Reading of Colonial Logic and the Play of Caricature in â€œHouseboy + Maidâ€ by Pramoedya Ananta Toer (Universitas Negeri Semarang, 2020)
Pramoedya Ananta Toerâ€™s works are highly distinguished for their strong realist characteristic and profound analysis of interactions among pre- and post- colonial human beings and their place in society. One of the works that portray such characteristics is â€œHouseboy + Maidâ€, the first story in Toerâ€™s collection Tales from Djakarta: Caricatures of Circumstances and Their Human Beings. In this research, post-colonialism and contrapuntal reading proposed by Edward Said are used as methods to interpret a literary work whose narration is about two characters who live in post-colonial Indonesia, or rather post-revolutionary Indonesia. Their unfixed identities which are interrelated through the changing event of the plot indicates that their very destiny cannot be separated from the â€œpoliticality, sociality, and historicalityâ€ of much bigger entities.